Induction and Prevention of Severe Hyperammonemia in the spf(ash) Mouse Model of Ornithine Transcarbamylase Deficiency Using shRNA and rAAV-mediated Gene Delivery - Cunningham, Sharon C (Nature Publishing Group, 2011)
Urea cycle defects presenting early in life with hyperammonemia remain difficult to treat and commonly necessitate liver transplantation. Gene therapy has the potential to prevent hyperammonemic episodes while awaiting liver transplantation, and possibly also to avert the need for transplantation altogether. Ornithine transcarbamylase (OTC) deficiency, the most prevalent urea cycle disorder, provides an ideal model for the development of liver-targeted gene therapy. While we and others have successfully cured the spf(ash) mouse model of OTC deficiency using adeno-associated virus (AAV) vectors, a major limitation of this model is the presence of residual OTC enzymatic activity which confers a mild phenotype without clinically significant hyperammonemia. To better model severe disease we devised a strategy involving AAV2/8-mediated delivery of a short hairpin RNA (shRNA) to specifically knockdown residual endogenous OTC messenger RNA (mRNA). This strategy proved highly successful with vector-treated mice developing severe hyperammonemia and associated neurological impairment. Using this system, we showed that the dose of an AAV rescue construct encoding the murine OTC (mOTC) cDNA required to prevent hyperammonemia is fivefold lower than that required to control orotic aciduria. This result is favorable for clinical translation as it indicates that the threshold for therapeutic benefit is likely to be lower than indicated by earlier studies.